Formação de professores da educação básica no âmbito da cibercultura - Corrêa, Janaina Martins (2019)
This Critical-Reflective report presents the intervention research carried out at the municipal school, in the municipality of Santa Vitória do Palmar, during the training in the Professional Master in Education, (RS), through an applied research aimed at training of teachers for cyberculture.The aim of the study was to provide digital application workshops for teachers of a municipal public school on the principles of cyberculture, seeking to evaluate if the intervention corroborates the teaching practice. In the intervention research the main concepts that underpinned it were the continuing education of teachers in cyberculture, the mobility and ubiquity to which we are inserted, and how the use of digital applications as a tool in educational practice occurred. From March to June 2019, five face-to-face meetings were held with digital workshops. Nineteen teachers from different classes of elementary school that work in the school participated. The intervention was basically structured by presenting the digital resource to the teachers, exploring its operation and building a reflection on its pedagogical use. In each meeting a digital resource was worked with the intention of the teachers to organize activities for the class they taught, according to their area of activity. In the whatsapp group, we exchanged information about videos and reports about experiences of the use of digital resources in educational practice. This feature allowed us a closer approach and provided the opportunity to share new knowledge. For the evaluation of the intervention, the teachers used some digital resource, which they knew during the training, in the class they chose according to their area of expertise. The analysis of the results of the intervention research was based on the construction of the analysis categories: the “use of digital applications as a tool in educational practice”, the “mobility and ubiquity”, and the “continuous teacher education in cyberculture”. According to the workshops held and the active participation of the intervention research participants, it was found that the teachers recognized that they could use their mobile devices and not only the school computer lab in the elaboration of their lesson plans contributing to the process. teaching and learning. They realized that we are immersed in the digital society, where cyberculture brings us to new times, where teachers can appropriate these means and use them in educational spaces. Cyberculture has contributed to the creation of new information, in which everyone can produce knowledge and share it collaboratively in digital media. It is in the different digital spaces that knowledge is produced in cyberculture, producing learning networks in a space where there is mobility and ubiquity. Thus, the intervention research contributed to highlight the need for change in educational practice, with regard to the inclusion of digital resources that we are linked daily.